Adult acquired flatfoot deformity: an update in classification. Issue 1 (February 2023) - Li, James; Pasapula, Chandra; Dhukaram, Vivekanandan
Abstract: Adult acquired flatfoot deformity (AAFD) involves a complex spectrum of pathologies, arising primarily from failure of static restrains, leading to collapse of the medial longitudinal arch and further subsequent deformities in the foot. The landmark paper and classification by Johnson et al. proposed that pathology in the posterior tibial tendon (PTT) was key in the development of AAFD. Since then, the understanding of AAFD has evolved and advanced. Multiple structures aside from the PTT, such as the spring ligament, plantar fascia and deltoid ligament, have been identified to play a similarly key role in disease development and progression. Classification systems have also evolved to incorporate this new understanding. These include modifications to Johnson's classification (Myerson, Bluman) as well as new systems which aim to incorporate modern thinking, capture the wide spectrum of presentations or utilize modern advancements in imaging modalities. Current classification systems continue to aid understanding and management of AAFD, despite their increasing complexity. Future classifications should aim to provide a succinct way to describe and understand AAFD, as well as guiding prognosis and management.